2021
DOI: 10.3389/fmolb.2021.725044
|View full text |Cite
|
Sign up to set email alerts
|

Where the Aryl Hydrocarbon Receptor Meets the microRNAs: Literature Review of the Last 10 Years

Abstract: The aryl hydrocarbon receptor (AhR) is an environmentally responsive ligand-activated transcription factor, identified in the ‘70s for its toxic responses to halogenated polycyclic aromatic hydrocarbons, such as dioxin. Recently, AhR has been recognized as engaged in multiple physiological processes in health and diseases, particularly in the immune system, inflammatory response, tumorigenesis, and cellular differentiation by epigenetic mechanisms involving miRNAs. However, there is still scarce information ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…Metabolites such as tryptamine (TRP), 3-methylindole (3MI), indole-3-acetaldehyde, IA, indole-3-aldehyde, indole acrylic acid, kynurenine, KA, XA and 5-hydroxyindoleacetic acid (5-HIAA) are ligands for AhR [56,57]. AhR is expressed throughout the body, but highest levels are found in the intestine, lung and skin, and it has been shown to regulate the immune system through several mechanisms [58] such as regulation of the differentiation of Th17 and Treg cells (see Figure 4) [59,60]. Bridging microbial metabolites and inflammation are several human receptors affecting the immune system such the aryl hydrocarbon receptor (AhR) and the pregnane X receptor (PXR) [55].…”
Section: Indole Pathwaymentioning
confidence: 99%
“…Metabolites such as tryptamine (TRP), 3-methylindole (3MI), indole-3-acetaldehyde, IA, indole-3-aldehyde, indole acrylic acid, kynurenine, KA, XA and 5-hydroxyindoleacetic acid (5-HIAA) are ligands for AhR [56,57]. AhR is expressed throughout the body, but highest levels are found in the intestine, lung and skin, and it has been shown to regulate the immune system through several mechanisms [58] such as regulation of the differentiation of Th17 and Treg cells (see Figure 4) [59,60]. Bridging microbial metabolites and inflammation are several human receptors affecting the immune system such the aryl hydrocarbon receptor (AhR) and the pregnane X receptor (PXR) [55].…”
Section: Indole Pathwaymentioning
confidence: 99%
“…PM2.5 may also promote PLA2R1 exposure by activating AhR on podocytes ( Li et al, 2018b ). And AhR is believed to be involved in various responses such as immune inflammation by altering the epigenetic mechanism of miRNAs ( Disner et al, 2021 ). However, there are few studies on this process in PMN.…”
Section: Composition and Mechanism Of Particulate Matter 25mentioning
confidence: 99%
“…Furthermore, exploring the possible multiple molecular gene-targets of miR-21, miR-122, miR-731, and miR-26 overexpressed by Tn P we concluded that, through this miRNA pathway, Tn P can regulate many genes in one pathway or even multiple cross-pathways, generating a tremendous impact on a complex regulatory network and, consequently, on the magnitude of neurogenesis and inflammation ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%